Relationship between Fast Food Consumption, Sedentary Lifestyle, and Physical Activity with Body Mass Index (BMI) among Students of Madrasah Aliyah Alkahiraat Pusat Palu Post-Covid-19 Pandemic - Rakhman, Aulia; Hamid, Megawati ABD.; Nurulfuadi, Nurulfuadi; Nadila, Devi; Aiman , Ummu (Journal of Health and Nutrition Research, 2025)
The prevalence of obesity in Indonesia is 31.0%, which means that many Indonesians have obesity problems, including teenagers. Palu City is ranked tenth out of 33 provinces, with a percentage of 32.9%. Fast food consumption, sedentary lifestyle, and physical activity affect Body Mass Index (BMI). This study aims to determine the relationship between fast food consumption, sedentary lifestyle, and physical activity and the Body Mass Index (BMI) of grade X and XI students of MA Alkhairaat Pusat Palu. The research method used is quantitative with a cross-sectional study design. The study population was 246, and a sample of 159 respondents was used using a proportional random sampling technique. Data collection was conducted using FFQ, ASAQ, and physical activity questionnaires. Data were analyzed using the Chi-Square statistical test. The univariate analysis results of respondents with abnormal BMI were 64 people (40.3%), and those with normal BMI were 95 people (59.7%). Based on bivariate analysis, the results of variables that have a relationship with Body Mass Index (BMI) are fast food consumption (p = 0.000). In contrast, variables that have no relationship with Body Mass Index are sedentary lifestyle (p = 0.917), and physical activity (p = 0.256). It is expected that adolescents can adopt a healthy lifestyle under the principles of balanced nutrition.